Thermokarst in Siberian ice-rich permafrost: Comparison to asymmetric scalloped depressions on Mars. - Ulrich, Mathias; Günther, Frank; Morgenstern, Anne; Schirrmeister, Lutz (PANGAEA, 2011)
This data set provides a high-resolution digital elevation model (DEM) of a thermokarst depression (~7 km²) on ice-complex deposits in the Arctic Lena Delta, Siberia. The DEM based on a geodetic field survey and was used for quantitative land surface analyses and detailed description of the thermokarst depression morphology. Detailed morphometrical analyses, volume calculations, and solar radiation modeling were performed and statistically analyzed by Ulrich et al. (2010) to investigate the asymmetrical thermokarst depression development and directed lake migration previously proposed by Morgenstern et al. (2008). Furthermore, the high-resolution DEM in combination with satellite data allowed detailed analyses of spatial and temporal landscape changes due to thermokarst development (Günther, 2009).
High-resolution digital elevation model (DEM) of a thermokarst depression in Siberian ice-rich permafrost deposits
Keywords: Comment; File size; Kurungnakh_Alas; Kurungnakh Island, Lena Delta, Siberia; Remote Sensing of POlar Non-glaciated and Sensitive Environments; RESPONSE; Sampling on land; Uniform resource locator/link to file